The Effectiveness of Baby Massage to Reduce Cold Cough Symptoms - Nopita Yanti; Nurhaida Br Kaban; Dona Martilova (Science Midwifery, 2022)
Cold cough is an upper respiratory tract disorder that most often affects infants and children. Very young babies will be infected very easily, transmission still occurs for someone who has a cold often hold his nose due to the itch or blow his nose. If you don't wash your hands immediately, it will become a source of infection. Cold cough is a primary infection of the nasopharynx and nose which often affects infants and children (RI Ministry of Health, 2021). Treatment efforts are being made to prevent pneumonia and ISPA (Upper Respiratory Tract Infection) as well as to overcome complaints such as symptoms of cough and cold, namely through medical (conventional) and alternative (traditional) treatment in line with scientific developments (Atmojo, 2012). This was an analytic survey study with a cross sectional approach. The study population was infants aged 0 - 12 months with 28 infants aged 0-12 months as the sample. It used a questionnaire as the instrument. The results showed that baby massage effectively reduced cold cough in 24 respondents (85%) and it was not effective in reducing cough cold symptoms for 4 respondents (15%). The conclusion, Baby message had an effect on reducing symptoms of cold cough in infants aged 0-12 months in RB Hadijah Medan.